東南極プリンス・オラフ海岸，あけぼの岩の変成作用 - 馬場, 壮太郎; 外田, 智千; 亀井, 淳志; 北野, 一平; 本吉, 洋一; Prayath, Nantasiun; Nugroho, Setiawan; Davaa-ochir, Dashbaatar; Sotaro, Baba; Tomokazu, Hokada; Atsushi, Kamei; Ippei, Kitano; et al. (2017)
第8回極域科学シンポジウム/個別セッション：[OG] 極域地圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object